Determinants of gender gaps in youth employment in urban Mozambique - Jana Bischler; Eva-Maria Egger; Paul Jasper; Ivan Manhique (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In this study, we explore the correlates of the employment gender gap among urban youth in Mozambique. Young people are confronted with simultaneous decisions about education, work and family life influenced by social norms around gender roles. Using data from a panel of individuals in 2017 and 2020, aged between 15-25 years in 2017, that covers information on education, employment, fertility, social life, gender norms and more, we observe an increase of 10 percentage points in the raw employment gender gap over time to the disadvantage of young women. Exploiting the longitudinal nature of our data, we apply two methods to assess the main correlates of this gap, an Oaxaca-Blinder decomposition on first-differenced data and a data-driven individual-level fixed-effects LASSO approach. Both analyses reveal that young women face a significant trade-off between work and time spent with reproductive activities and that the labour market seems to reward better education only for men.
Keywords: J13; J16; J71; O55; 330; gender gap; employment; decomposition; LASSO; Mozambique